Asthenosphere flow modulated by megathrust earthquake cycles - Barbot, Sylvain (2019)
Subduction megathrusts develop the largest earthquakes, often close to large populationcenters. Understanding the dynamics of deformation at subduction zones is therefore important to betterassess seismic hazards. Here I develop consistent earthquake cycle simulations that incorporate localizedand distributed deformation based on laboratory-derived constitutive laws by combining boundary andvolume elements to represent the mechanical coupling between megathrust slip and solid-state flow in theoceanic asthenosphere and in the mantle wedge. The model is simplified, in two dimensions, but may helpthe interpretation of geodetic data. Megathrust earthquakes and slow-slip events modulate the strain ratein the upper mantle, leading to large variations of effective viscosity in space and time and a complexpattern of surface deformation. While fault slipand flow in the mantle wedge generate surfacedisplacements in the same, that is, seaward, direction, the viscoelastic relaxation in the oceanicasthenosphere generates transient surface deformation in the opposite, that is, landward, directionabove the rupture area of the mainshock. Aseismic deformation above the seismogenic zone may bechallenging to record, but it may reveal important constraints about the rheology of the subducting plate.